An analytical approach of nonlinear buckling behavior of longitudinally compressed carbon nanotube‐reinforced (CNTR) cylindrical shells with CNTR stiffeners in thermal environment. Issue 4 (28th December 2021) - Dong, Dang Thuy; Nam, Vu Hoai; Phuong, Nguyen Thi; Ly, Le Ngoc; Duc, Vu Minh; Van Tien, Nguyen; Minh, Tran Quang; Hung, Vu Tho; Quan, Pham Hong
Abstract: Nonlinear buckling and postbuckling of longitudinally compressed carbon nanotube‐reinforced (CNTR) cylindrical shells stiffened by longitudinal or circumferential CNTR stiffeners in thermal environments surrounded by elastic medium are presented in the present study. Five linear distributions of CNT are considered for the shell‐stiffener structure system and they are modeled by innovation homogenization technique for CNTR stiffeners. Based on the classical Donnell thin shell theory with von Karman's nonlinearities and the Galerkin procedure, the governing equations can be built to analyze the critical buckling compression and postbuckling compression‐deflection and compression‐shortening behavior. The noticeable effects of volume fraction of CNTs, shell‐foundation interaction stiffnesses, uniformly distributed temperature, and geometric properties of stiffened cylindrical shells on the critical buckling compression and compression‐deflection and compression‐shortening postbuckling behaviors of stiffened CNTR cylindrical shells are obtained and remarked in numerical examinations. Abstract : Nonlinear buckling and postbuckling of longitudinally compressed carbon nanotube‐reinforced (CNTR) cylindrical shells stiffened by longitudinal or circumferential CNTR stiffeners in thermal environments surrounded by elastic medium are presented in the present study. Five linear distributions of CNT are considered for the shell‐stiffener structure system and they are modeled by innovation homogenization technique for CNTR stiffeners.…